First report on parasites of European beavers in the Slovak Republic - Bystrianska, Júlia; Papajová, Ingrid; Šmiga, Ľubomír; Šoltys, Jindřich; Majláthová, Viktória; Majláth, Igor; Gomboš, Filip; Kleban, Ján (Parasitology research, 2021)
European beaver (Castor fiber L. 1758) is the biggest rodent living in Europe. It is a semi-aquatic animal known for building dams and burrows. European beaver is a potential host for a wide range of parasites and other infectious diseases. In Slovakia, there is an increasing number of beavers but the data about their parasitic fauna are missing. Our work is the first documentation about the beaver's parasitofauna in Slovakia. In a 1-year study, we collected and examined 19 beaver fecal samples from the vicinity of beaver burrows inhabiting three particular localities at the Danube, Topľa, and Laborec rivers in Slovakia. In these fecal samples, 4 different species of intestinal endoparasites were detected as follows: oocysts of Cryptosporidium, cysts of Giardia, eggs of Stichorchis subtriquetrus, and eggs and larvae of Travassosius rufus. Parasites were confirmed only in samples collected at river Topľa. Based on our results, we can conclude that European beaver can be an important source of parasitic contamination of surface waters especially in the localities shared by people.
Keywords: Feces; Protozoans; Cryptosporidium; Cryptosporidiosis; Europe; Paramphistomatidae; Parasites; Evropa; Slovak Republic; Oocysts; Beaver; oocysty; řeky; Rivers; Giardiasis; paraziti; Slovakia; Slovenská republika; ženské pohlaví; Rodentia; zvířata; feces; hlodavci; trichostrongyloidóza; giardiáza; Trichostrongyloidea; Helminths; Trichostrongyloidiasis; Female; kryptosporidióza; Giardia; Animals